Las líneas de base en el mar Mediterráneo: ¿discrecionalidad o arbitrariedad en la acción estatal? (Revista Española de Derecho Internacional, 2007)
The breadth of the maritime zones under national jurisdiction is to be measured from baselines. The rules for drawing baselines are contained in the 1982 United Nations Convention on the Law of the Sea. These rules are too ambiguous. They allow excessive baseline claims, which can extend national jurisdiction significantly seaward in a manner that prejudices international interests. The practice of Mediterranean States in establishing baselines is examined in light of these rules.